2019
DOI: 10.1002/anie.201903455
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Strategy for Highly Diastereo‐ and Enantioselective Synthesis of 2,3‐Dihydrobenzofuran‐Based Tricyclic Scaffolds

Abstract: 2,3‐Dihydrobenzofurans are key pharmacophores in many natural and synthetic bioactive molecules. A biocatalytic strategy is reported here for the highly diastereo‐ and enantioselective construction of stereochemically rich 2,3‐dihydrobenzofurans in high enantiopurity (>99.9% de and ee), high yields, and on a preparative scale via benzofuran cyclopropanation with engineered myoglobins. Computational and structure‐reactivity studies provide insights into the mechanism of this reaction, enabling the elaboration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 50 publications
1
45
1
Order By: Relevance
“…The aminoacidic replacement strategy (Scheme 30, pathway a), in which protein structure rearrangements and changes in the active site shape are responsible for non-natural activities, has been extensively studied [101][102][103][104][105][106][107] and reviewed 99,[108][109][110][111] and it will be not discussed herein. This review only discusses the catalytic activity of artificial biomolecules, which were obtained by inserting a synthetic catalyst into a bio-scaffold.…”
Section: Artificial Iron Porphyrinoid Biocatalystsmentioning
confidence: 99%
“…The aminoacidic replacement strategy (Scheme 30, pathway a), in which protein structure rearrangements and changes in the active site shape are responsible for non-natural activities, has been extensively studied [101][102][103][104][105][106][107] and reviewed 99,[108][109][110][111] and it will be not discussed herein. This review only discusses the catalytic activity of artificial biomolecules, which were obtained by inserting a synthetic catalyst into a bio-scaffold.…”
Section: Artificial Iron Porphyrinoid Biocatalystsmentioning
confidence: 99%
“…Although a number of natural enzyme classes represent key components of the biocatalytic toolbox for organic synthesis (e.g., hydrolases, ketoreductases, transaminases) [1,4,18,19], we and others have reported that heme-containing enzymes and proteins are functional biocatalysts for "abiological" carbene transfer reactions, including olefin cyclopropanation [20][21][22][23][24][25][26][27][28][29], Y-H carbene insertion (where Y = N, S, B, or Si) [30][31][32][33][34][35][36], C-H functionalization [37][38][39][40][41], aldehyde olefination [42,43], and others [44,45]. In particular, engineered myoglobins (Mbs) have emerged as particularly selective and versatile scaffolds for promoting a variety of carbene-mediated transformations useful for the selective construction of new carbon-carbon and carbon-heteroatom bonds [23][24][25][26][27][28][29]31,32,35,36,38,39,42,…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the products shown there, the Fasan group has extended the scope of the methodology to include fused cyclopropyl-benzofurans and lactams. 47,48 The diverse nature of the products generated from these studies highlight the direction that biocatalysis will take in the coming years, producing scaffolds with increasing complexity through less synthetic steps than is possible with other methods.…”
Section: Engineered Metalloenzyme Cyclopropanationmentioning
confidence: 99%